2021
DOI: 10.1097/wnr.0000000000001708
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the connection network of whole-brain fiber tracts in patients with Alzheimer’s disease have a tendency of lateralization

Abstract: Effect size was obtained by Cramer's Phi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hemispheric lateralization is a widely accepted organizational principle of the human brain. Brain lateralization was associated with neurodevelopment [ 93 , 94 ], aging [ 95 , 96 ], cognition [ 97 , 98 ], emotion [ 99 , 100 ], and neuropsychiatric disorders, such as schizophrenia [ 101 , 102 ], depression [ 103 , 104 ], dementia [ 105 ], Alzheimer’s disease [ 96 , 106 ] and PD [ 107 , 108 ]. Heldmann et al [ 109 ] found that white matter microstructural abnormalities were only detected in the left hemisphere in the PD risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Hemispheric lateralization is a widely accepted organizational principle of the human brain. Brain lateralization was associated with neurodevelopment [ 93 , 94 ], aging [ 95 , 96 ], cognition [ 97 , 98 ], emotion [ 99 , 100 ], and neuropsychiatric disorders, such as schizophrenia [ 101 , 102 ], depression [ 103 , 104 ], dementia [ 105 ], Alzheimer’s disease [ 96 , 106 ] and PD [ 107 , 108 ]. Heldmann et al [ 109 ] found that white matter microstructural abnormalities were only detected in the left hemisphere in the PD risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the influence of AD, some connections of neurons would be damaged, resulting in information transmission barriers and corresponding symptoms [30]. Therefore, the network-based classification research can be categorized into classification by extracting DTI parameters from fiber bundles [31][32] and classification by analyzing brain networks [33][34][35][36].…”
Section: Relevant Researchmentioning
confidence: 99%